Penerapan Pendekatan Culturally Relevant Teaching (CRT) Dalam Pembelajaran Teks Laporan Hasil Observasi Pada Siswa Kelas VIII SMP Negeri 8 Palembang - Andriyani, Irma; Agustina, Juaidah (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The research was conducted at SMP Negeri 8 Palembang, precisely in class VIII 3, this activity involved 36 students using the CRT approach in learning the observation result report text based on culture. Qualitative descriptive research is used to examine the condition of natural objects. This research uses data collection techniques such as observation, interviews and documentation. Data analysis includes data collection, data delivery, and drawing conclusions. Data collection at the research location was carried out through observation, interviews and documentation, then the data that had been obtained was reduced or selected. Based on the research results, it shows that the application of the CRT approach in learning the observation result report text in class VIII 3 of SMP Negeri 8 Palembang succeeded in increasing learning motivation, enthusiasm for learning and student participation. It can be said to be successful because this approach is appropriate to apply during the learning process of the observation result report text material. Apart from that, the results of observations, interviews, video documentation and photos of learning, as well as the text of the observation results report show that the implementation of the CRT approach has been successfully applied to Palembang culture. Students can get to know and love their culture.